2000
DOI: 10.1046/j.1440-0960.2000.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis in dentistry

Abstract: Allergic contact dermatitis (ACD) in dentistry may affect dentists and orthodontists, technicians, nurses and patients. Changes to dental practice in recent years have altered the reported frequencies of allergens causing ACD in both dental personnel and patients. Allergic contact dermatitis to medicaments, metals and glutaraldehyde were previously common allergens in dentistry; however, widespread adoption of rubber gloves by staff has resulted in a significant increase in ACD to glove allergens in both denta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
3
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 41 publications
1
37
3
3
Order By: Relevance
“…26 Acrylic monomers can cause irritant contact dermatitis as well as allergic contact dermatitis reactions. 27 Our research found that for dental technicians the primary source of adverse reactions was acrylic resin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Acrylic monomers can cause irritant contact dermatitis as well as allergic contact dermatitis reactions. 27 Our research found that for dental technicians the primary source of adverse reactions was acrylic resin.…”
Section: Discussionmentioning
confidence: 99%
“…This describes the typical clinical pattern of contact dermatitis where the first, second and third fingertips of the non-dormant hand often demonstrate a dry, chronic dermatitis with deep fissures and erythema. 26 Further investigative work is required to determine the type of dermatitis experienced by dental technicians to enable comparisons with other surveys. Wearing gloves whilst handling acrylic monomers such as methyl methacrylate, rather than being protective, can increase the problems associated with contact dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…2 Allergic contact dermatitis (ACD) manifestations vary among individuals, and dental personnel is more likely to develop hand dermatitis, while patients with ACD caused by dental materials tend to develop stomatitis or cheilitis (type IV allergy) or contact urticaria (immediate -type I allergy). 3 The adoption of universal precautions in response to concerns about the transmission of human immunodeficiency virus (HIV) and other viruses has led to an increase in hand eczema from gloves and an increase in the frequency of irritant contact dermatitis. 3,4 In their work during dental treatment, dentists also use several products and handle polymer resin materials, which are known to be skin irritant, causing contact allergies and/or irritation of the skin and mucous membranes.…”
mentioning
confidence: 99%
“…3 The adoption of universal precautions in response to concerns about the transmission of human immunodeficiency virus (HIV) and other viruses has led to an increase in hand eczema from gloves and an increase in the frequency of irritant contact dermatitis. 3,4 In their work during dental treatment, dentists also use several products and handle polymer resin materials, which are known to be skin irritant, causing contact allergies and/or irritation of the skin and mucous membranes. 5 Additionally, frequent hand washing and the use of protective gloves for many hours per day contribute to an unfavorable environment for the skin of the hands.…”
mentioning
confidence: 99%
“…Ortodontik tedavi sırasında daha az sıklıkla da olsa braketlerin yapıştırılmasında kullanılan bonding ajanlarına, [47][48][49][50] ekstraoral apareylere, 50,51 dezenfektanlara ve antimikrobial ajanlara 51,52 karşı allerjik reaksiyonlar gelişebilmektedir. Ekstraoral apareyler nedeniyle oluşan reaksiyonlar apareylerin metalik, elastik kısımlarına veya doku ile temasta olan aparey parçalarına (Resim 2) bağlı olarak gelişebilmektedir.…”
unclassified